2013
DOI: 10.1177/0018720813501549
|View full text |Cite
|
Sign up to set email alerts
|

Human Performance Consequences of Stages and Levels of Automation

Abstract: Findings contribute to the body of research on adequate function allocation by providing an overall picture through quantitatively combining data from a variety of studies across varying domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
356
4
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 416 publications
(388 citation statements)
references
References 59 publications
22
356
4
6
Order By: Relevance
“…The negative consequences of disconnecting humans from direct guidance and control are primarily concentrated in three areas which have been identified in different application contexts: insufficient or excessive trust in the automation [9], the loss of manual and cognitive capabilities [10] and difficulties in maintaining an appropriate degree of situation and system awareness [11]. An inappropriate degree of confidence in the system can result in insufficient monitoring or use of automated systems.…”
Section: The Design Of Automated Systemsmentioning
confidence: 99%
“…The negative consequences of disconnecting humans from direct guidance and control are primarily concentrated in three areas which have been identified in different application contexts: insufficient or excessive trust in the automation [9], the loss of manual and cognitive capabilities [10] and difficulties in maintaining an appropriate degree of situation and system awareness [11]. An inappropriate degree of confidence in the system can result in insufficient monitoring or use of automated systems.…”
Section: The Design Of Automated Systemsmentioning
confidence: 99%
“…In particular, a vehicle equipped with Level 2 automation allows the driver to take both hands off the wheel and feet off the pedals, at least for brief periods of time (that time depending on the manufacturer). As the level of automation which takes over control of the vehicle increases, the chance for monitoring failures also increases [30]. But this does not seem to be true of increases in automation which support information acquisition.…”
Section: ) Driver As Supervisormentioning
confidence: 99%
“…But such is not the case if control over both of these is relinquished. Thus, despite instructions to monitor the roadway, there is every likelihood that the driver will fail to monitor adequately and all three necessary ingredients of situation awareness will suffer [30], thereby increasing the likelihood of a crash.…”
Section: ) Driver As Supervisormentioning
confidence: 99%
“…Degree of automation characterises the task's allocation of function, by defining the contribution of technologies in terms of level of automation (low, moderate, or high), and across each of the four stages of information processing (information acquisition, information analysis, decision & action selection, and action implementation; (Onnasch, et al, 2013). This analysis was documented for each identified technology, and then aggregated for each time step (as depicted in Figures 1-3).…”
Section: Topographicalmentioning
confidence: 99%
“…The metaanalysis carried out by Onnasch et al (2013) found that this effect is exacerbated in certain system designs, and a performance step change occurs when the design of automation shifts from allocation of information analysis, to decision and action selection. From the analysis of identified technologies, 'information analysis' was found to be the stage of information processing with the largest increase in allocation to technology between 2020 and 2050, followed closely by 'action selection'.…”
Section: Topographicalmentioning
confidence: 99%